2018
DOI: 10.1186/s13567-018-0550-x
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica induces Foxp3 T cell, proinflammatory and regulatory cytokine overexpression in liver from infected sheep during early stages of infection

Abstract: The expression of T regulatory cells (Foxp3), regulatory (interleukin [IL]-10 and transforming growth factor beta [TGF-β]) and proinflammatory (tumor necrosis factor alpha [TNF-α] and interleukin [IL]-1β) cytokines was quantified using real time polymerase chain reaction (qRT-PCR) in the liver of sheep during early stages of infection with Fasciola hepatica (1, 3, 9, and 18 days post-infection [dpi]). Portal fibrosis was also evaluated by Masson’s trichrome stain as well as the number of Foxp3+ cells by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…Increased expression of regulatory cytokines supports a role for Tregs in the generation of a suppressive environment which is favourable to parasite persistence. Furthermore, TGF-β is an essential cytokine in the development of fibrosis, as demonstrated in our previous study 33 .…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Increased expression of regulatory cytokines supports a role for Tregs in the generation of a suppressive environment which is favourable to parasite persistence. Furthermore, TGF-β is an essential cytokine in the development of fibrosis, as demonstrated in our previous study 33 .…”
Section: Resultssupporting
confidence: 56%
“…33 R 5′-AACGTGGGCTACCGGCTTGTTATTTGAGGC-3′73.6(99.56) IL-1β NM_001009465.2F 5′-GAAGCTGAGGAGCCGTGCCTACGAACA-3′68.81851.001Pacheco et al . 33 R 5′-CCAGCACCAGGGATTTTTGCTCTCTGTCC-3′69.0(99.85) FoxP3 NM_001144947.1F 5′-GCCCATCTGGCTGGGAAGATGGCCCAAACC-3′76.51660.991Pacheco et al . 33 R 5′- AGAGGTGCCTCCGCACGGCAAACAGG-3′76.2(99.16) IL-10 NM_001009327.1F 5′-TCAGCCGTGCTCTGTTGCCTGGTCTTCC-3′73.81240.999Pacheco et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the three species analyzed, while Foxp3-positive cells were found in the lesion sites of all individuals, the numbers were generally small. Experimental infection of F. hepatica in sheep Ovis aries have demonstrated that the number of regulatory T cells is significantly higher in the early stages of infection and decrease as the infection progresses, which has been speculated to be due to the parasite inducing a modulation in the host response to evade its immune system ( 48 ). The results of immunohistochemistry for Foxp3 in the analyzed cetaceans also suggested a chronic stage of the disease, which may be indicating a similar evading system in the trematodes of cetaceans to that of F. hepatica .…”
Section: Discussionmentioning
confidence: 99%
“…These complex parasite-derived molecules can interact with the immune system and inhibit the Th1-driven protective pro-inflammatory responses through the induction of M2 macrophages (9), mast cells (10), and Th2-type responses (11,12), and promote regulatory T (Treg) cell development (6,13). Thus, the induction of an ineffective immune response against this parasite allows the development of a chronic infection.…”
Section: Introductionmentioning
confidence: 99%